2001
DOI: 10.2307/3454898
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Blood Pressure and Hypertension with Lead Dose Measures and Polymorphisms in the Vitamin D Receptor and d-Aminolevulinic Acid Dehydratase Genes

Abstract: Evidence suggests that lead and selected genes known to modify the toxicokinetics of lead--namely, those for the vitamin D receptor (VDR) and delta-aminolevulinic acid dehydratase (ALAD)--may independently influence blood pressure and hypertension risk. We report the relations among ALAD and VDR genotypes, three lead dose measures, and blood pressure and hypertension status in 798 Korean lead workers and 135 controls without occupational exposure to lead. Lead dose was assessed by blood lead, tibia lead measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 48 publications
(88 reference statements)
1
12
0
Order By: Relevance
“…Both blood lead, which reflects recent exposure, and bone lead, which reflects cumulative exposure, have been associated with blood pressure increases. [27][28][29] Thus, it is unclear whether the adverse health effects of lead observed here were associated with current or cumulative exposures. In addition, because of declining lead levels in the decades before lead ascertainment in the present analysis, it is unclear whether the observed increased risk in mortality was due to lead exposure at baseline or lead mobilization from the skeleton.…”
Section: Discussionmentioning
confidence: 91%
“…Both blood lead, which reflects recent exposure, and bone lead, which reflects cumulative exposure, have been associated with blood pressure increases. [27][28][29] Thus, it is unclear whether the adverse health effects of lead observed here were associated with current or cumulative exposures. In addition, because of declining lead levels in the decades before lead ascertainment in the present analysis, it is unclear whether the observed increased risk in mortality was due to lead exposure at baseline or lead mobilization from the skeleton.…”
Section: Discussionmentioning
confidence: 91%
“…Hu et al [1994] point out that an increase in patella lead levels of 37 mg/g observed in construction workers are associated with a decrease of 11 g/L in hemoglobin even when blood lead concentrations were low (8.3 mg/dL, mean). Accumulation in bone is also associated with hypertension [Hu et al, 1996;Korrick et al, 1999;Lee et al, 2001;Rothenberg et al, 2002;Glenn et al, 2003] and reduced weight at birth [González-Cossío et al, 1997]. Therefore, the contribution of bonestored lead is important.…”
Section: Discussionmentioning
confidence: 99%
“…Chia et al 70 in a study of Vietnamese and Singaporean lead workers, showed that workers with the ALAD2 allele appeared more susceptible to the toxic effects of lead on renal function, especially at higher lead levels. Another study 71 among Koreans subjects did not find any association between ALAD genotype with blood pressure, but reported that subjects with the VDR B gene allele in hetero and homozygous combination had higher systolic and diastolic blood pressure as well as higher prevalence of hypertension. In spite of the above mentioned association of the varied genetic variability in lead toxicity, more research is needed to justify the assessment of these genetic polymorphisms in lead exposure screening and evaluation.…”
Section: Epidemiology General Incidence and Prevalencementioning
confidence: 92%